SPEECH SKILLS IN FUTURE PEDAGOGUES - Abdullaeva Dilorom Nomonova (Galaxy International Interdisciplinary Research Journal, 2023)
The concept of speech is closely related to the concept of communicative behavior of the teacher. The communicative behavior of the teacher is not only the process of speaking and giving information, but also the organization of speech that affects the relationship and work style between the teacher and the student, creating an emotional psychological environment for the communication between the pedagogue and the student, and the appropriate speech delicacy of the teacher. The teacher’s speech should meet certain requirements, that is, it should correspond to the necessary communicative qualities